Finiteness, subjunctives, and negation in English - Anderson, John M. (Adam Mickiewicz University, 2008)
This paper pursues the analysis of finiteness and subjunctives in English proposed in Anderson (2001b), in the context of the approach to finiteness adopted in Anderson (1997, 2001a, 2006b, 2007). Thus it defends the position that the Present-day English subjunctive is non-finite, if finiteness is equated with the capacity to license independent sentencehood. In particular, I present here some further evidence for such an analysis deriving from the syntax of negation. Specifically, the position of the negative with the “present” subjunctive is the position associated with the negating of a non-finite form. And positional behaviour under negation is also in accord with the idea that the subjunctive “periphrasis” with should, as well as the “past subjunctive” is also non-finite. The phenomena addressed are incompatible, however, with definitions of finiteness based on the presence of particular morphological categories.